Pedagogia organizacional: estudo baseado na teoria fundamentada (grounded theory) no Nordeste do Brasil - Silva, Luciano Lima da (2021)
This research talks about Organizational Pedagogy and the possibilities of the pedagogue's performance in corporate environments. It is understood that the specificity of the pedagogical work developed in the organizations will allow to give new meanings and formative meanings to the Pedagogy courses and to the profession of pedagogue. This study aims to investigate the prospects for the professional performance of educators in promoting learning in organizational spaces, in the Northeast Region. The methodological basis is based on: Strauss and Corbin (1990) and Charmaz (2009), who systematized the Grounded Theory Method, which employs circularity in the qualitative research process. As for the approach, the present study is of the exploratory type, considering that this aspect makes it possible to find evidence of a field with little systematized knowledge. The theoretical dialogue was built based on the references of Pedagogy, starting from Libâneo (2001) and Franco, Libâneo and Pimenta (2011), Non-School Education - Severo (2015, 2018, 2019), Business Pedagogy - Ribeiro (2007) and Holtz (1999), and organizational learning - Bitencourt (2010), among others. 14 (fourteen) pedagogues participated in the research, selected from the nine (9) states of the Northeast Region, being 04 in Paraíba, 01 in Pernambuco, 01 in Rio Grande do Norte, 01 in Ceará, 02 in Maranhão , 02 in Bahia, 01 in Piauí, 01 in Sergipe and 01 in Alagoas. As a tool for data production, it was used a structured questionnaire, applied by email and in person. The data analysis procedure was based on the open, axial and selective coding of the Grounded Theory, supported by the Atlas.ti 8.0 analysis software. The results of the research point out that the pedagogues who work in the organizational scope need to become aware of the specifics attributed to the function, appropriating better the pedagogical dimension that involves the development of learning for a simple process of training and change behavior based on competitive performance criteria. In addition, it was found that the educational practices of (as) teachers (as) are structured by means of network knowledge and skills, which occur transversely as they crisscross the knowledge of pedagogy and the specific knowledge of the organization. The substantive theory created from the analysis in the research exposes the theoretical and methodological elements necessary for the Pedagogy professional who wishes to enter organizational spaces, including demonstrating that the Pedagogy course must overcome the boundaries imposed by tradition, which reduces to training of basic education teachers, according to the social and professional representation that the educator can / should assume in the areas of training of learning in organizational scenarios.